Dieulafoy lesions causing upper gastrointestinal bleeding in children - N.Z. Mashavave; T.R. Govender; D.S. Harrison; A.P. Theron (Elsevier, 2019)
Since the description of Dieulafoy lesions, its' definition has broadened and now represents an acute process that occurs in adult and paediatric patients, with intra-gastric and extra-gastric locations. There are also multiple advancements in the non-operative management of such lesions. Prompt diagnosis and management is required for improved outcomes. Management is mainly dependent on the haemodynamic status of the patient and location of the lesion. Endoscopic diagnosis and the multiple endoscopic treatment options now available have made operative intervention less frequent. However, there are no current management guidelines for DLs in the paediatric population. We look at two patients in two Johannesburg tertiary institutions that presented with gastric and duodenal Dieulafoy lesions and the treatment strategies applied. One patient was managed successfully with haemostatic endo-clips. The other patient was initially managed with endoscopic adrenaline injections at four quadrants but later required a partial gastrectomy. Keywords: Dieulafoy lesion, Endoscopy, Paediatric, Upper gastrointestinal bleeding